2015
DOI: 10.1016/j.biomaterials.2014.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Localized delivery of mechano-growth factor E-domain peptide via polymeric microstructures improves cardiac function following myocardial infarction

Abstract: The Insulin like growth factor-I isoform mechano-growth factor (MGF), is expressed in the heart following myocardial infarction and encodes a unique E-domain region. To examine E-domain function, we delivered a synthetic peptide corresponding to the unique E-domain region of the human MGF (IGF-1Ec) via peptide eluting polymeric microstructures to the heart. The microstructures were made of poly (ethylene glycol) dimethacrylate hydrogel and bioengineered to be the same size as an adult cardiac myocyte (100×15×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Bearing in mind the above, our data suggesting an overexpression of IGF-1Ec by injured tissues, such as by the surrounding tissues in prostate cancer, is reminiscent of the preferential expression of IGF-1Ec post-skeletal muscle damage and that of the myocardium during the post-infarction period. [30][31][32][33][34][35][36] Interestingly, species-specific differences of hEc and mE actions may point to a possible different mode of actions at the receptor level. It has been reported that mE requires IGF-1R for its bioactivity, 36 while hEc appears to act in an IGF-1R independent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bearing in mind the above, our data suggesting an overexpression of IGF-1Ec by injured tissues, such as by the surrounding tissues in prostate cancer, is reminiscent of the preferential expression of IGF-1Ec post-skeletal muscle damage and that of the myocardium during the post-infarction period. [30][31][32][33][34][35][36] Interestingly, species-specific differences of hEc and mE actions may point to a possible different mode of actions at the receptor level. It has been reported that mE requires IGF-1R for its bioactivity, 36 while hEc appears to act in an IGF-1R independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mE requires IGF-1R for its bioactivity, 36 while hEc appears to act in an IGF-1R independent manner. 15,20,33 Thus, the residue rat position 23 of hEc is probably crucial for hEc receptor recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Neomycin delivered locally from microporous microrods might be advantageous in clinical use. MGF eluted over several days from PEGDMA microrods (Doroudian et al, 2014) improved cardiac function after ischemia injury (Peña, Pinney, Ayala, Desai, & Goldspink, 2015). PEGDMA microrods were loaded with high concentrations of neomycin and maintain release over 12 hr.…”
Section: Relevance For Wound Healingmentioning
confidence: 99%
“…As an example, hydrogel microrods can deliver an insulin like growth factor mimicking peptide to prevent unwanted cardiac remodeling and enhance survival in a post myocardial infarction mouse model [64]. Additionally, for neural regeneration, PLGA nanoparticles have been shown to deliver leukemia inhibitory factor to support the growth of dopaminergic cells for the regeneration of lost tissue observed in Parkinson's disease [65].…”
Section: Soluble Mediatorsmentioning
confidence: 99%